Analysis Of Village Building Index In Village Development In Kuala Sub-District - Ramly, Ar Royyan; Wahyuddin, Wahyuddin; Mursyida, Julli; Mawardati, Mawardati (Jurnal Ekonomi Pembangunan, 2019)
This study aims to analyze the village building index in the development of village in Kuala sub-district of Nagan Raya regency. This research is descriptive qualitative and quantitative. The object of this study is 17 villages in the region of Kuala sub-district, while the data used in this study is sourced from primary and secondary data derived from document review, observation, FGD, and interviews from 2015 to 2017. Data analysis technique using descriptive analysis in the form of tables and diagrams, while the quantitative analysis using multiple regression test with the dependent variable percentage of village fund accumulation 2015-2017, independent variables are Environmental Sensitivity Index, Economic Conditions Index, Healthy Family Index and Village Building Index. The results showed that the analysis of the use of village funds for development in Kuala sub-district positively influence. Then with the development of village infrastructure and empowerment, the status of villages in the region of Kuala sub-district increased with an average developing status of 71 percent and advanced village status of 23 percent.